2021
DOI: 10.1021/acsapm.1c00304
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Resistant Behavior of Poly(ethylene glycol)-Containing Polymers with Phosphonate/Phosphate Units on Stainless Steel Surfaces

Abstract: Stainless steel is used in a large variety of food and medical applications, where it is susceptible to adsorption of proteins and other materials on its surface, ultimately leading to biofouling. Here, we report the synthesis of a copolymer bearing both poly­(ethylene glycol) (PEG)-antifouling and phosphate-containing monomers, abbreviated as poly­(PEGMA-co-MEP), to be used as an easily applied nano-coating for a stainless steel substrate. Highly tenacious films could be easily deposited by dipping the stainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…These results are consistent with our previous work 14,44 where phosphonate based polymer layers have shown excellent stability upon rinsing under different rinsing conditions. Similar findings were observed in a recent study by Giamblanco et al 65 where they studied the stability of poly(ethylene glycol) copolymers with phosphonate units as surface tethering groups on an iron oxide surface in water, and the resultant films appeared stable.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with our previous work 14,44 where phosphonate based polymer layers have shown excellent stability upon rinsing under different rinsing conditions. Similar findings were observed in a recent study by Giamblanco et al 65 where they studied the stability of poly(ethylene glycol) copolymers with phosphonate units as surface tethering groups on an iron oxide surface in water, and the resultant films appeared stable.…”
Section: Resultssupporting
confidence: 93%
“…S10(a) † ). We showed in previous work, 14 that a PEO-phosphonate copolymer film deposited from water only formed a monolayer on stainless steel as measured by QCM-D.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Among the different polymers examined for this purpose, DHCs showed excellent antifouling effects. 357,360–362 As one example, Kousar et al 351 reported a nano-coating for a stainless steel substrate. In this work, they used copolymers based on poly(ethylene glycol) methyl ether methacrylate and 2-(meth acryloyloxy)ethyl phosphate (poly(PEGMA- co -MEP)), that was used also as an antifouling coating for covering steel surface (Fig.…”
Section: Introductionmentioning
confidence: 99%